Fellow Eye Involvement in Low Compliance Patient with Non-Arteritic Ischemic Optic Neuropathy: A Case Report - syntia nusanti; Dearaini Dearaini; Rasyidia Lakmita Putri; Rianti Wulandari Pratiwi (Majalah Oftalmologi Indonesia, 2022)
Introduction: The incidence of fellow eye involvement in non-arteritic anterior ischemic optic neuropathy (NAION) is 15% at 5 years after initial onset, although risk factors have not been identified. The aim of this article is to determine the risk factor that could influence the fellow eye involvement with NAION.  Case Report: A 72 year-old male presented with gradual painless vision loss in the left eye (LE) for 3 months. He did not have smoking habit. BCVA on the LE was 3/60 and RAPD was present. Funduscopic examination showed optic disc atrophy on LE. Humphrey test revealed altitudinal pattern on LE with visual field index (VFI) 63%. OCTA showed significant decreased capillary perfusion on LE retinal nerve fiber layer thinning and poor capillary perfusion on LE while the right eye (RE) was normal. Laboratory examination indicated diabetes mellitus, dyslipidaemia, and hypercoagulable state. He was prescribed antidiabetic medication, antithrombotic therapy, and statin. After a month, patient showed improvement in both ocular and laboratory examinations. He was advised to continue treatment until the next visit, but he didn’t comply. Two months later, patient was presented with painless vision loss, edematous optic disc, and altitudinal visual field defect in the RE. Laboratory examination also revealed unsatisfactory results. Discussion: Prior studies discovered that hypercoagulable states potentially contribute to NAION, presumably due to altered blood viscosity, which further leads to vascular occlusion. Our case showed hypercoagulable state patient with increased d-Dimer and fibrinogen level. Antithrombotic therapy was found beneficial to improve patient’s symptoms. However, he did not comply to therapy, thus vision loss of the fellow eye occurred. Conclusion: Non-compliant behaviour of patient could be the risk factor for fellow eye involvement.